Musicianship in the digital world: Interdisciplinary approach to bachelor’s education (Música Hodie, 2025)
The purpose of this study was to investigate the effects of computer technology on learning in music education and the integration of digital tools to develop students’ creativity, technical skills, and teamwork. The study involved an online survey of art students from Khmelnytskyi Humanitarian-Pedagogical Academy and Kyiv National University of Culture and Arts, which helped to collect quantitative data on their experience with digital audio workstations and music programmes. Quantitative and qualitative analyses were employed to process the data: statistical analysis of the surveys revealed general trends, and qualitative interpretation of the observations and projects revealed the specifics of using technology in teaching. 70% of participants reported major improvements in composition and arrangement skills due to the use of digital audio workstations, and 80% noted positive changes in teamwork thanks to online platforms. The study also found that 55% of participants felt that the integration of technology had given them the opportunity to experiment with new musical genres, and 75% said that learning had become more interactive and engaging thanks to digital tools. This underlined the significance of developing interdisciplinary skills that combine music education with information technology. The study has practical implications for teachers, as it emphasised the significance of adapting teaching strategies to the modern requirements of the music industry and developing new pedagogical approaches. The findings of this study can serve as a basis for improving curricula in music education and training professionals who can effectively use digital technologies in their work.